Ignatius the Deacon: on the Sacred Images - the Theology of a Hagiographer - O. IZOTOVA (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2015)
The author examines the theology of Ignatius the Deacon regarding the holy icons, a Byzantine author who wrote around the cusp of the eighth and ninth centuries. His theological perceptions are found in the lives of George of Amastris, Gregory the Decapolite, and the patriarchs of Constantinople Tarasius and Nicephoros, all of which he composed. These vitae belong to the genre of hagiographies in high style . They are composed using elegant phraseology and are replete with citations and theological argumentations. Thus, they aﬀord the researcher abundant material for reﬂ ection. Ignatius presents a detailed apology for the holy images. He theorizes on the way they act upon those who view them. Most importantly, he introduces the concept of the so called living images of virtue which are created by the saints in their own persons. Ignatius raises various arguments in favor of the veneration of the icons and refers to the imagery employed by the proponents of iconodoulic theology.